2021
DOI: 10.33425/2639-9512.1062
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mouse Embryonic Fibroblasts (MEFs) into Cardiomyocytes Using Human-Derived Cardiac Inducing RNA (CIR)

Abstract: The present study explores an RNA we have discovered in human heart that induces differentiation of mouse embryonic stem cells and human induced pluripotent stem cells into cardiomyocytes in vitro. We have designated this RNA as Cardiac Inducing RNA or CIR. We now find that CIR also induces mouse embryonic fibroblasts (MEF) to form cardiomyocytes in vitro. For these studies, human-derived CIR is transfected into MEF using lipofectamine. The CIR-transfected mouse fibroblasts exhibit spindle-shaped cells, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our hypothesis posits that LncRNA-CIR6 may induce the differentiation of endogenous stem cells in the heart or the injected hUCMSCs into cardiogenic cells. Furthermore, studies have demonstrated that cardiac-inducing RNA-6 (CIR-6) can induce the direct differentiation of murine fibroblasts into cardiomyocytes in vitro [29]. Therefore, we hypothesize that cardiogenic cells not only derive from the differentiation of MSCs induced by LncRNA-CIR6 but may also transform from myocardial fibroblasts under specific conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Our hypothesis posits that LncRNA-CIR6 may induce the differentiation of endogenous stem cells in the heart or the injected hUCMSCs into cardiogenic cells. Furthermore, studies have demonstrated that cardiac-inducing RNA-6 (CIR-6) can induce the direct differentiation of murine fibroblasts into cardiomyocytes in vitro [29]. Therefore, we hypothesize that cardiogenic cells not only derive from the differentiation of MSCs induced by LncRNA-CIR6 but may also transform from myocardial fibroblasts under specific conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Our hypothesis posits that LncRNA-CIR6 may induce the differentiation of endogenous stem cells in the heart or the injected hUCMSCs into cardiogenic cells. Furthermore, studies have demonstrated that cardiac-inducing RNA 6 (CIR6) can induce the direct differentiation of murine fibroblasts into cardiomyocytes in vitro [ 43 ]. Therefore, we hypothesize that cardiogenic cells not only derive from the differentiation of MSCs induced by LncRNA-CIR6 but may also transform from myocardial fibroblasts under specific conditions.…”
Section: Discussionmentioning
confidence: 99%